Anthropometric variables among Sri Lankan elite male athletes of team games - Buvanendiran, P. (University of Jaffna, 2022)
The modern trend in the preparation of elite sportsmen is to proceed scientifically and take the help of allied sciences to achieve top-level performance in respective sports and games. The objective of the study was to compare the differences among selected anthropometric measurements of Sri Lankan elite male athletes who belonged to basketball, football, handball, and volleyball team games. To achieve the purpose of the study eighty (N=80, age 18-32 years) elite male athletes were selected from Colombo, Sri Lanka (basketball (n=20), football (n=20), handball (n=20), and volleyball (n=20) on purposive sampling. The data were collected on anthropometric variables such as standing height, body weight, arm length, thigh girth and leg length. Collected data were statistically analysed by using One-way ANOVA. And Scheffe’s post hoc test was applied wherever the F-ratio (sig=0.05) was found to be significant. The results of the study revealed that there were significant differences existed in all the selected anthropometric measurements [standing height (F=6.901), body weight (F-15.475), Arm length (F=3.783), Thigh Grith (F=4.251), Leg Length (F=12.756)]. Hence it was concluded the volleyball players were taller, heavier and have greater arm and leg lengths than other players in standing height, body weight, arm length, and leg length. And football players were found to be greater in thigh girth.
Keywords: Anthropometric; Elite athletes; Team Games; Arm length; Body Weight